Ultra-high performance liquid chromatography-tandem mass spectrometry assay for simultaneous determination of 22 marker compounds in traditional herbal medicine Ojeoksan - Kim, Hee Seo; Baek, Seung Hoon (Journal of Pharmaceutical and Biomedical Analysis, 2024)
Traditional herbal medicines (THMs) have long been in use worldwide and are considered safe for use as tonics or complementary treatments for many diseases. Advanced quality control methods for THMs are required in the regulatory framework of modern medicines. In this study, an ultra-high performance liquid chromatography-tandem mass spectrometry assay was established for the simultaneous determination of 22 marker compounds in Ojeoksan (OJS), which is composed of 15 herbal substances. All marker compounds were analyzed within 20 min and successfully identified via scheduled multiple reaction monitoring. The method validation revealed excellent performance characteristics of the method such as specificity, linearity, sensitivity, precision, and accuracy, demonstrating its suitability for intended use. The developed method was applied to samples of commercial OJS tablet and soft-extract dosage forms. The 14 marker compounds corresponding to 12 component herbal substances were determined in the samples; ephedirine, albiflorin, paeoniflorin, ferulic acid, hesperidine, neohesperidin, cinnamic acid, platycodin D, 6-gingerol, atractylenolide III, glycyrrhizin, honokiol, decursin, and magnolol. A fast and easy assay method with sufficient discrimination power was established. As a novel assay, this method can contribute to the quality control of OJS products.
Keywords: Chromatography, High Pressure Liquid; Drugs, Chinese Herbal; Herbal Medicine; Medicine, Korean Traditional; Plant Extracts; Plants, Medicinal; Quality Control; Reproducibility of Results; Tablets; Tandem Mass Spectrometry; Marker compound; Ojeoksan; Simultaneous analysis; Traditional herbal medicines; UHPLC-MS/MS; Validation